Strategies for Membership Growth in Nonprofit Organizations: Evidence from Lions Clubs New Zealand - Teck, Tan Seng; Keow, Loy Kwee; Geok, Lim Swee; Fernandez, Reynold Tom; Liau, Chee How; Sonar, Pradeep (International Review of Management and Marketing, 2026)
Nonprofit organizations, particularly service-based groups like Lions Clubs, play a vital role in community development and social engagement. However, many such organizations in New Zealand face challenges related to declining membership, ageing demographics, and evolving communication patterns. Understanding the factors influencing membership attraction and retention is essential for ensuring long-term sustainability. This study employed a mixed-method research design combining quantitative and qualitative approaches. A structured survey using Likert-scale questions was administered to Lions Club members to assess motivations, awareness, and marketing effectiveness. Additionally, semi-structured interviews with selected participants and direct observations of club activities were conducted to provide deeper contextual insights. Statistical analysis, including descriptive statistics, chi-square tests, correlation, and factor analysis, was performed using SPSS. The findings indicate a predominance of older, long-term members, highlighting sustainability concerns. Altruistic motivations such as community service and helping others, along with social factors like companionship and relationship-building, significantly influence both joining and retention. Awareness-generating activities show a strong association with membership attraction. Traditional marketing strategies, especially word of mouth and local newspapers, were found to be more effective than digital platforms. Strong positive correlations were observed between initial motivations and long-term engagement factors. The study emphasizes the need for adaptive strategies that integrate traditional and digital outreach methods while targeting younger demographics. Strengthening social engagement and community-oriented values can enhance both recruitment and retention, ensuring the sustainability of nonprofit service organizations.